Video Profile Sebagai Media Penunjang Promosi Pada Sdk Penabur Gading Serpong - Dewi Immaniar Desrianti; Giandari Maulani; Dana Krisdiana (CCIT Journal, 2019)
The tight competition between schools in the era of globalization today, requires that the school Ivory Serpong Sower SDK to do the marketing strategy as attractive as possible, in order to enhance the new prospective learner interests as well as improve the quality of and professionalism in the management of the school. It is a promotional effort is used to market products or services to the public, so that they are more familiar with or know the product or service being marketed. Current media information and promotions that use the SDK Sower Ivory Serpong still be printed in the form of banners, brochures and more, so there are still many who have not yet learned about SDK Sower Gading Serpong. The purpose of this research is to inform and promote school SDK Sower Ivory Serpong. Based on a needs analysis is required of media promotion in the form of a video profile, to support information and promotion more attractive and effective by using the software Adobe Premier and Adobe Photoshop. Research methods used namely collecting data through observation, interviews and literature studies, Media Production and concept i.e. preproduction, production and postproduction. Through the design of Video media Profile of this SDK Sower Ivory Serpong can better known to many people and attracting parents to enroll his son in schools – SDK Sower Ivory Serpong